2020
DOI: 10.1590/s1982-21702020000300014
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the GNSS Positioning Performance Under Influence of the Ionospheric Scintillation

Abstract: The ionosphere may not only degrade the accuracy of the GNSS positioning but also reduce its availability because there is a high dependence between signal losses and ionospheric irregularities. Irregularities in the Earth's ionosphere may produce rapid fluctuations in phase and amplitude. These rapid fluctuations are called ionospheric scintillation. Thus, loss of signal can occur due to the effects of diffraction and refraction, which cause a weakening in the signal received by the GNSS receivers. In this wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Because of its vulnerability and sensitivity, a slight change in the geomorphic ecology of the mountain area will involve changes for many reasons, such as space, environment, location, climate, and human factors [ 14 ]. Since ancient times, the relationship between people and geological environment has started from ignoring the geological environment, developed to damaging the geological environment, and finally transformed into the ability to restore and develop the geological environment [ 15 ]. Today's one-size-fits-all urbanization development mode, extensive land development and preemptive land excavation, and development and utilization have aggravated the geological and ecological crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its vulnerability and sensitivity, a slight change in the geomorphic ecology of the mountain area will involve changes for many reasons, such as space, environment, location, climate, and human factors [ 14 ]. Since ancient times, the relationship between people and geological environment has started from ignoring the geological environment, developed to damaging the geological environment, and finally transformed into the ability to restore and develop the geological environment [ 15 ]. Today's one-size-fits-all urbanization development mode, extensive land development and preemptive land excavation, and development and utilization have aggravated the geological and ecological crisis.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it is suggested that new ionospheric models should be developed to perform better TEC spatial interpolation. Caldeira et al (2020) evaluated the magnitude of ionospheric scintillation in Brazil and the performance of PPP under its influence during the period of high solar activity of the current cycle (24), through the Spearman correlation analysis and the Wavelet periodogram. Three-year time series (2012 to 2014) of the S 4 index and three-dimensional Mean-Squared Error (3D MSE) recorded by three Brazilian stations with different ionospheric conditions were considered: Palmas (10.18°S 48.33°W, geomagnetic longitude 7.61°S, near the geomagnetic equator), Presidente Prudente (low-latitude region, under the EIA), and Porto Alegre (midlatitude region).…”
Section: Gnss Positioning Techniques With Emphasis On New Signalsmentioning
confidence: 99%